Forecasting Errors, Diversification and Inventory Fluctuations - Thompson, Howard E. (Academy of Management Journal, 1966)
The behavior of inventory changes in the individual firm has important implications for the economy as well as for the firm itself. For the firm, fluctuations in inventory change induce fluctuations in cash flows and have an important bearing on the inventory decision. On the aggregate level, fluctuations in inventory change affect national income and employment. This study represents a theoretical description of the dynamic effects of errors in the sales forecast as they are transmitted to fluctuations in inventory. A production planning rule, a characterization of forecasting errors, and the sales pattern are the basic elements of the model. Bach element, of course, could have been formulated in many different ways. By studying only the error which produces a constant ratio between the expected change in sales and the actual change we can express inventory change and production rate as linear difference equations. Then if sales are expressed as a sinusoidal, an analytic solution for the pattern of inventory change and production rate can be easily determined and the relationship between fluctuations in sales and either of the former can be expressed as the gain, or amplification, of the system. In addition to facilitating an analytic solution, these simplifications lead to a measure of fluctuations and add insight into more complex structures.1